Efectos del Zinc, Calcio y Boro sobre el rendimiento del maíz (Zea mays L.) en la zona de Las Delicias, del cantón de Simón Bolívar, Provincia Guayas - Arzube Alvarado, Sergio Javier (2020)
The present work was carried out on the land of the Las Delicias farm located in the Simón Bolívar - Guayas canton. For sowing, the corn hybrid “NS-70 was used. The objective of the work was to evaluate the application of various doses of Calcium, Boron and Zinc in the production of corn. For the effect, the Sett and Keylate Zinc products were used, in a “Random Complete Block” design with three repetitions. The sowing of the crop was carried out manually in experimental plots of 20 m2. The analysis of variance established the statistical significance and the evaluation of means was done with the Tukey significance test at 5 %. The variables evaluated at the end of the trial were: plant height, insertion height, days to flowering, days to harvest, diameter of ears, length of ears, grain weight, yield per hectare, partial productivity per nutrient (PPN) and analysis economic. The data show that the variables: plant height, insertion height, days to flowering, days to harvest, length of ears, diameter of ears and number of grains, did not reach statistical significance. The grain weight had its highest average applying Sett 1,0 l/ha + Keylate Zinc 0,75 l/ha, Sett 1,0 l/ha + Keylate Zinc 0,5 l/ha and Sett 1,0 l/ha + Keylate Zinc 1,0 l/ha. The highest grain yield was achieved by applying Sett 1,0 l/ha + Keylate Zinc 0,75 l/ha (8939,16 kg/ha). The partial productivity values per nutrient PPN were higher for Calcium and Boron applying Sett 0,5 l/ha + Keylate Zinc 0,5 l/ha. The Zinc values in contrast were high in the plants treated with. Sett 1,0 l/ha + Keylate Zinc 0,5 l/ha. The Sett 1,0 l/ha + Keylate Zinc 0,75 l/ha treatment presented the highest utility and net benefit.